Effect of Substrate Temperature and Annealing on the Electrical and Optical Properties of Zinc Phthalocyanine Thin Films - Gopinathan, T.G.; Menon, C.S. (Asian Journal of Chemistry, 2016)
Zinc phthalocyanine thin films are prepared at different substrate temperatures at a base pressure of 10–5 m bar. Thin films are coated on glass substrates by thermal evaporation technique. Samples of equal thickness coated at room temperature are subjected to post-deposition annealing at different temperatures in air and vacuum for 1 h. The electrical conductivity studies are carried out by keeping the samples in a conductivity cell at a pressure of 10–3 mbar in the temperature range of 300–500 K. The electrical conductivity is plotted as a function of absolute temperature. The conduction mechanism is observed to be hopping. The thermal activation energy is calculated and is observed to vary with annealing temperature and substrate temperature. The optical absorption studies are done in the UV-Visible region. The optical band gap energies of the samples are calculated.